Proceedings of the 2020 Conference on Human Information Interaction and Retrieval 2020
DOI: 10.1145/3343413.3377971
|View full text |Cite
|
Sign up to set email alerts
|

Conversations with Documents: An Exploration of Document-Centered Assistance

Abstract: The role of conversational assistants has become more prevalent in helping people increase their productivity. Document-centered assistance, for example to help an individual quickly review a document, has seen less significant progress, even though it has the potential to tremendously increase a user's productivity. This type of document-centered assistance is the focus of this paper. Our contributions are three-fold: (1) We first present a survey to understand the space of document-centered assistance and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Previous studies have found that small screen devices like smartphones are usually used on-the-go, leading to fragmented user attention [4,78]. However, this phenomenon requires further investigation, under various interaction modalities (e.g., smartphone screen vs. voice [97]) and contexts (e.g., walking vs. driving [174]).…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Previous studies have found that small screen devices like smartphones are usually used on-the-go, leading to fragmented user attention [4,78]. However, this phenomenon requires further investigation, under various interaction modalities (e.g., smartphone screen vs. voice [97]) and contexts (e.g., walking vs. driving [174]).…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…The questions would be different from factoid questions and chitchat, because here the focus would be on relevant information from that specific document. 65 This category seems to have a big scope for understanding, reviewing, and inferring knowledge from documents.…”
Section: Existing Accessibility-driven Solutions For Pdf Documentsmentioning
confidence: 99%
“…BVIP should be able to satisfy their information needs without having to sequentially go through all the website content and structure -a process that can be time consuming and frustrating for screen reader users [19]. This support is rooted in the ongoing efforts in conversational Q&A [13] and document-centered digital assistant [18]. The idea is to support BVIP users to perform natural language queries (NLQ) on the contents of websites, and to inquire about the properties defined in the website's metadata.…”
Section: Characterising Conversational Browsing Supportmentioning
confidence: 99%